Relative effects of statin therapy on stroke and cardiovascular events in men and women: secondary analysis of the stroke prevention by aggressive reduction in cholesterol levels (SPARCL) study - Goldstein, Larry B.; Amarenco, Pierre; LaMonte, Marian; Gilbert, Steven; Messig, Michael; Callahan, Alfred; Hennerici, Michael G.; Sillesen, Henrik; Welch, K. Michael A. (Stroke, 2008)
Background and Purpose: In SPARCL, treatment with atorvastatin 80 mg daily reduced stroke risk in patients with recent stroke or TIA and no known coronary heart disease by 16% versus placebo over 4.9 years of follow-up. The purpose of this secondary analysis was to determine whether men and women similarly benefited from randomization to statin treatment.Methods— The effect of sex on treatment-related reductions in stroke and other cardiovascular outcomes were analyzed with Cox regression modeling testing for sex by treatment interactions.Results— Women (n=1908) constituted 40% of the SPARCL study population. At baseline, men (n=2823) were younger (62.0±0.21versus 63.9±0.27 years), had lower systolic BPs (138.1±0.35 versus 139.5±0.47 mm Hg), higher diastolic BPs (82.2±0.20 versus 81.0±0.25 mm Hg), more frequently had a history of smoking (73% versus 38%), and had lower total cholesterol (207.0±0.54 versus 218.9±0.67 mg/dL) and LDL-C levels (132±0.45 versus 134±0.57 mg/dL) than women. Use of antithrombotics and antihypertensives were similar. After prespecified adjustment for region, entry event, time since event, and age, there were no sex by treatment interactions for the combined risk of nonfatal and fatal stroke (treatment Hazard Ratio, HR=0.84, 95% CI 0.68, 1.02 in men versus HR=0.84, 95% CI 0.63, 1.11 in women; treatment×sex interaction P=0.99), major cardiac events (HR=0.61, 95% CI 0.42, 0.87 in men versus HR=0.76, 95% CI 0.48, 1.21 in women; P=0.45), major cardiovascular events (HR=0.78, 95% CI 0.65, 0.93 in men versus HR=0.84, 95% CI 0.65, 1.07 in women; P=0.63), revascularization procedures (HR=0.50, 95% CI 0.37, 0.67 in men versus HR=0.76, 95% CI 0.46, 1.24 in women; P=0.17), or any CHD event (HR=0.54, 95% CI 0.41, 0.72 in men versus 0.67 95% CI 0.46, 0.98 in women; P=0.40).Conclusion— Stroke and other cardiovascular events are similarly reduced with atorvastatin 80 mg/d in men and women with recent stroke or TIA.